Full N,N-Methylation of 4,4′-Methylenedianiline with Dimethyl Carbonate: A Feasible Access to 4,4′-Methylene bis(N,N-Dimethylaniline) - Zegang Qiu; Kunjie Wang; Zhiqin Li; Tao Li; Jinhao Bai; Chanjuan Yin; Xiushen Ye; Haining Liu (Journal of Chemistry)
The full N,N-methylation of 4,4′-methylenedianiline (MDA) with dimethyl carbonate (DMC) was investigated. The yield of the major product 4,4′-methylene bis(N,N-dimethylaniline) (MBDMA) reached as high as 97% over NaY catalyst at 190°C for 6 h. The catalyst could be used for two more times with acceptable MBDMA yields higher than 90%. The main by-products were identified as three N-methylated derivatives. Surprisingly, the formation of the N-methoxycarbonylation product was extremely restrained, which could be produced in high yields of 98% on zinc acetate catalyst. Furthermore, the reaction pathway to the major product MBDMA was proposed. Finally, a feasible synthetic route of 4,4′-methylene bis(N,N-dimethylaniline) (MBDMA) was established, featuring a high yield, mild reaction conditions, and simple operations.